2013
DOI: 10.1002/bjs.9088
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hepatectomy for recurrent colorectal metastases

Abstract: Repeat hepatectomy for recurrent colorectal metastases offers long-term survival in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
92
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 53 publications
19
92
0
14
Order By: Relevance
“…These data agree with the conclusions of a recent meta-analysis of studies assessing repeat hepatectomy for recurrent CRLM [25]. While this earlier analysis found no significant difference in overall survival between the single resection and repeat resection groups when all studies were evaluated, repetition of analyses to include just high-quality studies [11,12,14,15] or just studies with greater than 500 cases demonstrated that repeat resection was significantly associated with improved overall survival following metastasectomy. In agreement with this, Saiura et al recently found the performance of repeat resection to be independently associated with prolonged overall survival following metastasectomy [26].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These data agree with the conclusions of a recent meta-analysis of studies assessing repeat hepatectomy for recurrent CRLM [25]. While this earlier analysis found no significant difference in overall survival between the single resection and repeat resection groups when all studies were evaluated, repetition of analyses to include just high-quality studies [11,12,14,15] or just studies with greater than 500 cases demonstrated that repeat resection was significantly associated with improved overall survival following metastasectomy. In agreement with this, Saiura et al recently found the performance of repeat resection to be independently associated with prolonged overall survival following metastasectomy [26].…”
Section: Discussionsupporting
confidence: 87%
“…Studies to date, however, have yielded conflicting results regarding the influence of repeat hepatectomy for CRLM upon longterm survival [11][12][13][14][15][16][17]. A notable finding of this study was that repeat hepatectomy was significantly associated with improved overall and cancer-specific survival following metastasectomy, along with established prognostic factors including tumor number and margin status.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The frequencies of repeat hepatectomies for recurring CRC in patients with initially unresectable metastases, observed between January 1990 and January 2010 in a French hospital, were reported by Wicherts et al 174 ( Table 115). In total, 1.4 operations were carried out per patient.…”
Section: Laparoscopic Surgery (£)mentioning
confidence: 79%